Optimasi kondisi proses pemurnian (Degumming- netralisasi) minyak nyamplung dengan response surface methodology - Ika Amalia Kartika; Muhamad Ryan Pratama (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Calophyllum seeds produce high-yielding non-edible oils, so Calophyllum plants have great potential as a source of biofuels. To meet biofuel quality standards, crude Calophyllum oil must first be refined. This study investigated the temperature and time optimization in refining crude Calophyllum oil extracted using a binary solvent, i.e., n-hexane and methanol. The experiment was performed in a central composite design using independent variables temperature (70-90°C) and time (10-30 minutes) with 11 runs, and the optimization was performed in response surface method. The best model for optimizing oil yield was the second-order polynomial model, with optimal oil yield (44.62%) obtained at a temperature of 81.4°C and a time of 19.9 minutes. When the oil yield was optimized with the acid value of the oil as the boundary condition, the optimum oil yield and acid values were 44.44% and 2.43 mg KOH/g, obtained at a temperature and time of 83.4°C and 19.7 minutes. Model validation at this optimum purification condition resulted in the actual oil yield (46.40%) conformed passably to its prediction. In addition, the purified oil obtained from this model validation had good characteristics and matched the predicted results.